Women upward—sex differences in uphill performance in speed climbing, ski mountaineering, trail running, cross-country skiing, and cycling - Millet, G. P.; Raberin, A.; Faiss, R.; Giovanelli, N.; Galindo, T.; Place, N.; Sandbakk, Ø. (International Journal of Sports Physiology and Performance, 2024)
Introduction: Women have generally lower body size and lean- to fat-mass ratio, lower maximal anaerobic power due to a lower muscle mass, and fewer fast-twitch fibers, although they can show higher resistance to fatigue or greater metabolic flexibility than men. These factors are well known and explain the sex differences in endurance sports such as distance running (10%-12%). Several of these factors—particularly the differences in body composition and skeletal-muscle characteristics—may directly impact vertical displacement and uphill performance. However, there is a lack of sex-difference reports in sports with uphill locomotion.